RESEARCH THIS AIM FOR KNOWING LEVEL PROFITABILITY FINANCE ON COOPERATIVE SAVE IT BORROW (KSP) TRI DHARMA ARTHA BASED RATIO PROFITABILITY. - Ida Sariyani; Afdal Mazni; Febriyanto Febriyanto (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
Research this aim for knowing level profitability finance On Cooperative Save It Borrow (KSP) Tri Dharma Artha based ratio profitability. Research this use analysis quantitative, results analysis ratio finance cooperative on analysis ratio profitability showing level optimal on Cooperative Save It Borrow (KSP) Tri Dharma Artha on period 2012-2015. In the calculate profitability something cooperative needed report finance KSP Tri Dharma Artha that concerned, composed from balance sheet, income statement report finance that showing circumstances company that composed from assets, debt and capital company on moment certain. Based results research and discussion could concluded that: 1) On analysis NPM ksp tri dharma artha could visible that on year 2012 amount 5,16%, year 2013 amount 4,99%, year 2014 amount 10,16% and year 2015 amount 9,82%. Will but if referring on standard cooperative indonesia that is amount 20%. So NPM on coorperative tri dharma artha this not yet reach results that optimist. 2) Analysis ROA ksp tri dharma artha could visibli that on year 2012 amount 0,94%, year 2013 amount 0,94%, year 2014 amount 1,75%, and year 2015 amount 1,59%. Will but if referring on standard cooperative indonesia that is amount 20%. So ROA on coorperative tri dharma artha this not yet reach results that optimist. 3) Analysis ROE ksp tri dharma artha could visibli that on year 2012 amount 10,91%, year 2013 amount 10,75%, year 2014 amount 17,92%, and year 2015 amount 19,84%. Will but if referring on standard cooperative indonesia that is amount 20%. So ROE on coorperative tri dharma artha this not yet reach results that optimist.